2013
DOI: 10.1007/s11540-013-9246-9
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Distribution of Potato Pests and Diseases in Kenya

Abstract: Potato plays an important role in food security in Kenya but yields are low (<10 t/ha), and this is partly attributed to the lack of healthy planting material. This study is the first wide-scale survey to determine the occurrence and distribution of common potato pests and diseases in Kenyan seed (certified and quality declared) and ware crops. Potato crops growing on 101 farms in 21 districts were examined. Approximately 36% of plants in farmers' fields sampled both during the long rains (main potato-growing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 17 publications
1
43
0
Order By: Relevance
“…Low incidences of PLVR, PVM and PVY as well as zero detection of PVA and PVX in RSS tuber samples may be attributed to restricted spread of these viruses due to the absence of insect vectors and alternate hosts in the experimental site (Djilani-Khouadja et al, 2010). Were et al (2013) also reported that PVS as the most detected virus followed by PVY, PVX, and PLRV in samples collected from potato growing districts in Kenya. Yardimci et al (2015) also reported that PVS and PVY as the most prevalent potato viruses in potato growing areas in Turkey when ELISA tests were conducted on tubers.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Low incidences of PLVR, PVM and PVY as well as zero detection of PVA and PVX in RSS tuber samples may be attributed to restricted spread of these viruses due to the absence of insect vectors and alternate hosts in the experimental site (Djilani-Khouadja et al, 2010). Were et al (2013) also reported that PVS as the most detected virus followed by PVY, PVX, and PLRV in samples collected from potato growing districts in Kenya. Yardimci et al (2015) also reported that PVS and PVY as the most prevalent potato viruses in potato growing areas in Turkey when ELISA tests were conducted on tubers.…”
Section: Discussionmentioning
confidence: 91%
“…High incidences of PVS may have occurred due to its ability to pass through tissue culture process which is usually adopted in production of certified seeds (Were et al, 2013) or because PVS is mainly transmitted mechanically, it could have spread by farmers during farm operations (Gul et al, 2013). Low incidences of PLVR, PVM and PVY as well as zero detection of PVA and PVX in RSS tuber samples may be attributed to restricted spread of these viruses due to the absence of insect vectors and alternate hosts in the experimental site (Djilani-Khouadja et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, [45] reported that potato tuber moth to be the most lethal pest unlike cutworms as reported in this study. In addition, [46] reported potato aphids as the most lethal field pests especially in the spread of viral diseases. Cutworms were the most damaging field pest since they cause damage at planting leading to poor field establishment [19].…”
Section: Seed Potato Production Practices By Small-scale Farmersmentioning
confidence: 99%
“…Depletion of soil nutrients such as nitrogen and phosphorus has been a growing problem for bean production in East Africa (Kimani et al, 2007(Kimani et al, , 2008; Ayuke et al, 2011). Insect pests such as the black bean aphid Aphis fabae have been transmitting viral diseases (Beebe, 2012;Were et al, 2013), while fungal pathogens such as Colletotrichum lindemuthianum cause anthracnose disease of beans in East Africa (Beebe, 2012;Kharinda, 2013). These factors have been complicated by the fact that local cultivars that are widely grown by smallholder farmers in East Africa have been succumbing to a complex of biotic and abiotic stresses (Otsyula et al, 2004;Ojiem et al, 2006;Kharinda, 2013).…”
Section: Introductionmentioning
confidence: 99%